Ambient fine and coarse particulate matter pollution and respiratory morbidity in Dongguan, China. (March 2017) - Zhao, Yiju; Wang, Shengyong; Lang, Lingling; Huang, Caiyan; Ma, Wenjun; Lin, Hualiang
Abstract: We estimated the short-term effects of particulate matter (PM) pollution with aerodynamic diameters ≤2.5 μm (PM2.5 ) and between 2.5 and 10 μm (PMc ) on hospital outpatient visits due to overall and specific respiratory diseases, as well as the associated morbidity burden in Dongguan, a subtropical city in South China. A time-series model with quasi-Poisson link was used to examine the association between PM pollution and morbidities from respiratory diseases, COPD, asthma and pneumonia in Dongguan during 2013–2015. We further estimated the morbidity burden (population attributable fraction and attributable morbidity) due to ambient PM pollution. A total of 44, 801 hospital outpatient visits for respiratory diseases were recorded during the study period. Both PM2.5 and PMc were found to be significantly associated with morbidity of overall respiratory diseases, COPD, and asthma. An IQR (interquartile range) increase in PM2.5 at lag03 day was associated with 15.41% (95% CI: 10.99%, 20.01%) increase in respiratory morbidity, and each IQR increase in PMc at lag03 corresponded to 7.24% (95% CI: 4.25%, 10.32%) increase in respiratory morbidity. We did not find significant effects of PM2.5 and PMc on pneumonia. Using WHO's guideline (25 μg/m 3 ) as reference concentration, about 8.32% (95% CI: 5.90%, 10.86%) of respiratory morbidity (3727, 95% CI: 2642, 4867, in morbidity number) were estimated to be attributed to PM2.5, and 0.86% (95% CI: 0.50%, 1.23%) of respiratory morbidity, representing 385 (95% CI: 225, 551) hospital outpatient visits, could be attributed to coarse particulate pollutant. Our study suggests that both fine and coarse particulate pollutants are an important trigger of hospital outpatient visits for respiratory diseases, and account for substantial respiratory morbidity in Dongguan, China. Graphical abstract: Highlights: We estimated respiratory morbidity burden due to fine and coarse PM pollutants. Both PM2.5 and than coarse PM pollutants were associated with respiratory morbidity. Substantial morbidity burden can be attributable to fine and coarse particles. Abstract : Both fine and coarse particulate matter pollutants were found to be associated with increased respiratory morbidity, particularly from COPD and asthma. Substantial respiratory morbidity burden could be attributable to these two pollutants in Dongguan, China.